DEVELOPING ARABIC LANGUAGE LEARNING MULTIMEDIA - Tri Wardati Khusniyah; Ali Muhtadi (Jurnal Kependidikan, 2018)
This study was aimed at describing the problems in the application of Arabic as the language of daily communication, the level of active Arabic language skills, and the level of need for multimedia learning development to improve the students' Arabic speaking ability. The sample of the study was the principal and students of grades VII to grade IX at an Islamic Boarding School in Yogyakarta. The sample was chosen by using random sampling method. The data collection was carried out by interviewing the principals and conducting open questionnaires aimed at the students. The data then were analyzed using qualitative descriptive method. The results show that there had been a decrease in the application of Arabic for everyday conversation due to problems experienced by students such as difficulty in Arabic language, lack of motivation among students, lack of school support for the application of Arabic, and the media used were not feasible. The level of need for the development of Arabic learning multimedia in order to practice the ability to speak Arabic for students is very high with a percentage of 100%.PENGEMBANGAN MULTIMEDIA PEMBELAJARAN BERBAHASA ARABAbstrakPenelitian ini bertujuan mendeskripsikan masalah-masalah dalam penerapan bahasa Arab sebagai bahasa komunikasi sehari-hari, tingkat kemampuan berbahasa Arab aktif, dan tingkat kebutuhan pengembangan multimedia pembelajaran untuk melatih kemampuan berbicara bahasa Arab bagi siswa. Sampel penelitian adalah kepala sekolah dan siswa kelas VII sampai kelas IX SMP Islamic Boarding School Bina Umat Yogyakarta yang dipilih menggunakan metode random sampling. Pengumpulan data dilakukan dengan wawancara yang ditujukan kepada kepala sekolah dan angket terbuka yang ditujukan kepada siswa. Data dianalisis dengan teknik deskriptif kualitatif. Hasil penelitian menunjukkan bahwa telah terjadi penurunan dalam penerapan bahasa Arab untuk percakapan sehari-hari disebabkan oleh masalah-masalah yang dialami oleh siswa seperti susahnya materi bahasa Arab, kurangnya motivasi di kalangan siswa, kurangnya dukungan pihak sekolah terhadap penerapan bahasa Arab, dan media yang digunakan juga belum mampu melatih kemampuan berbicara bahasa Arab. Tingkat kebutuhan pengembangan multimedia pembelajaran bahasa Arab untuk melatih kemampuan berbicara bahasa Arab bagi siswa sangat tinggi dengan persentase 100%..